Legal Framework for Protecting Children from Commercial Sexual Exploitation - Abdul Rahman; Ayub, Zainal Amin; Ratnawati, Ratnawati (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
This study offers a critical analysis of the legal framework and policy measures aimed at protecting children from Commercial Sexual Exploitation of Children (CSEC) in South Sulawesi, Indonesia. Despite the ratification of international agreement and the enactment of domestic laws, such as Law No. 35 of 2014, the enforcement of these laws is inconsistent. This inconsistency is attributed to legal ambiguities, limited institutional capacities, and cultural attitudes that normalize exploitation. Employing a socio-legal approach, this research integrates legal analyses with field interviews to investigate the causes, manifestations, and legal management of CSEC. The findings reveal systemic shortcomings, such as the absence of specific criminalization for child prostitution and trafficking in the Criminal Code, ineffective implementation of regional regulations, and poor collaboration among law enforcement agencies, NGOs, and government entities. CSEC continues to be a pervasive issue, with victims often misidentified as offenders. The study advocates for legal harmonization with international standards, enhanced institutional collaboration, heightened public awareness, and community-based monitoring initiatives. It stresses the urgent need for child-rights-centric legal reforms to tackle the socio-cultural factors driving exploitation and to strengthen the protective role of both the state and society.